Dose optimisation of first-line tuberculosis drugs using therapeutic drug monitoring in saliva: feasible for rifampicin, not for isoniazid. Issue 4 (22nd October 2020) - van den Elsen, Simone H.J.; Akkerman, Onno W.; Wessels, Mireille; Jongedijk, Erwin M.; Ghimire, Samiksha; van der Werf, Tjip S.; Bolhuis, Mathieu S.; Touw, Daan J.; Alffenaar, Jan-Willem C.
The persisting worldwide burden of tuberculosis (TB) is worrisome. In 2018, an estimated 10 million individuals developed TB and 1.45 million infected individuals died [1]. The increase in drug resistance is an important point of concern. Resistance can be acquired by inappropriate drug management, noncompliance and insufficient drug exposure [2, 3]. The last is frequently described for the first-line TB drugs rifampicin and isoniazid due to large interindividual pharmacokinetic variability [3]. Therapeutic drug monitoring (TDM) can be used to verify drug exposure and adjust individual drug dosages if needed [4]. Therapeutic drug monitoring using saliva samples is feasible for rifampicin, despite low penetration, but is not feasible for isoniazid, which showed inexplicable highly variable saliva/serum concentration ratios https://bit.ly/2yAS2Jc